Efficacy and Side Effects of Letrozole Over Clomiphene citrate for Ovulation Induction of the Patients with PCOS: A Randomized Controlled Trial - Begum, Poly; Shaha, Dipti Rani; Hassan, Md Kamrul; Zeba, Dilruba (Faridpur Medical College Journal, 2021)
Clomiphene citrate (CC) has been the drug of choice for the treatment of anovulatory subfertility in women with polycystic ovarian syndrome (PCOS) for a long time. Despite high ovulation rate of CC, its pregnancy rate is low. Letrozole, an aromatase inhibitor has been considered as an alternative of CC but its effectiveness is yet controversial. Our aim was to compare the efficacy and side effects of Letrozole over CC. This randomized control clinical trial was conducted in Diabetic Association Medical College and Hospital, Faridpur, Bangladesh from January 2018 to December 2019. A total of 160 women diagnosed as PCOS by Rotterdam criteria seeking treatment of subfertility were included in the study. Participants were randomly divided into two groups. Group A got Letrozole and Group B got CC as treatment. Transvaginal ultrasonogram (TVS) was performed on 12 to 13th day of the cycle to see the details of the follicles and the endometrium. The demographic information of the participants and the side effects of the drugs were recorded. Successful pregnancies were followed up for 12 weeks. Ovulation rate was almost similar among the participants of both of the groups. But monofo licular development and pregnancy rate were significantly higher among the Letrozole group (p = 0.004 and p = 0.008 respectively). Multifo licular development, multiple pregnancy, and abortion rate were significantly higher in the CC group. Patients who took Letrozole had significantly higher endometrial thickness than CC group. Both of the groups reported relatively similar incidence of side effects. Due to the higher pregnancy rate and lower incidence of abortion or multiple pregnancy, Letrozole can be an effective alternative to CC for the treatment of anovulatory subfertility of the PCOS patients. Faridpur Med. Coll. J. 2020;15(2): 69-73